Meta-Analysis: Effectiveness of Reciprocal Teaching Model on Mathematics Learning Outcomes - Laia, Harun Onesimus; Dasari, Dadan (Universitas Wiralodra, 2025)
One learning approach that can be applied to learning mathematics is reciprocal teaching because it is efficient in helping students become independent learners and developing students' courage in expressing opinions. Many studies have discussed Reciprocal Teaching with mathematics learning outcomes in primary and secondary schools with different conclusions. This study aimed to determine the effect of the Reciprocal Teaching model on students' mathematics learning outcomes. This study used a meta-analysis, a statistical analysis method that synthesizes data from several studies to obtain stronger findings. The sample in this study were articles that met the inclusion criteria and obtained as many as 8 articles. Data were analyzed using JASP V-0.18 software. The results showed that the Reciprocal Teaching model affected students' mathematics learning outcomes, with an effect size of 1.07 and a high effect size category. However, this analysis did not include some related studies because they did not meet the inclusion criteria. Therefore, further research using a larger sample size and a wider variety of studies is needed to gain a more thorough understanding.